MEMORIA COLECTIVA Y CEREMONIAS CONMEMORATIVAS. UNA APROXIMACIÓN TEÓRICA - Díaz Arias, David (2011)
This paper proposes an analysis on the relationship between collective memory and commemorative ceremonies. It proposes that studying commemorative ceremonies as rituals allows investigator on nation-building to find new ways to understand national festivals and the process of construction of collective memory. Commemorative ceremonies are understood as heterogeneous, cultural productions that show hegemony up but also counterculture movements. Therefore, this work criticizes the theory on the invention of tradition and that of the lieux de mémoire. By doing so, it theorizes that analysis on rituals lead us to identify the way heterogeneous memories are created through performances.